HUMAN MECHANIZATION AS REFLECTED IN STEVEN SPIELBERG'S ARTIFICIAL INTELLIGENCE (2001): A SOCIOLOGICAL APPROACH. - KHOTIMAH P, KHUSNUL (2011)
This study is aimed to reveal the human mechanization as reflected in Artificial Intelligence movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on sociological approach. This research is qualitative research. Type of data of the study is literary taken from two data sources: primary and secondary. The primary data source is taken from Artificial Intelligence movie directed by Steven Spielberg that released in 2001. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions, first based on structural analysis of each elements, it shows that the narrative and the technical elements of the movie are related to each other and form the unity into good quality of a movie. Second, based on sociological analysis, there is close relation between the movie production and the underlying social reality. The major factors that contribute to the production are the issues about the possibility of the loss of human control over computer-based intelligence. Robots may look more human instead of men do.